2023
DOI: 10.7189/jogh.13.04116
|View full text |Cite
|
Sign up to set email alerts
|

High-risk pregnancy in India: Prevalence and contributing risk factors – a national survey-based analysis

Periyasamy Kuppusamy,
Ranjan Kumar Prusty,
Deepali Prakash Kale

Abstract: Background High-risk pregnancies (HRP) place women and their offspring at the highest risk for morbidity and mortality. Maternal and medical risks increase pregnancy risk and complications during pregnancy and childbirth. Here, we reported the current prevalence of high-risk pregnancies among Indian women, which is defined through various factors such as maternal, lifestyle, medical, current health risk and adverse birth outcomes.Methods This is a cross-sectional study based on secondary data from India's Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…We will exclude pregnant women who have a history of using any assisted reproductive technology or who have been diagnosed with a high-risk pregnancy where complications are anticipated. [44] We will also exclude pregnant women with occupation or lifestyle factors that are reported by previous studies to be sources of exposure to high levels of PM. [45][46][47] Mothers with pregnancy loss, preterm delivery; and term neonates with birth asphyxia and diagnosed congenital anomalies will be identi ed using relevant records and dropped from further follow-up.…”
Section: Study Populationmentioning
confidence: 99%
“…We will exclude pregnant women who have a history of using any assisted reproductive technology or who have been diagnosed with a high-risk pregnancy where complications are anticipated. [44] We will also exclude pregnant women with occupation or lifestyle factors that are reported by previous studies to be sources of exposure to high levels of PM. [45][46][47] Mothers with pregnancy loss, preterm delivery; and term neonates with birth asphyxia and diagnosed congenital anomalies will be identi ed using relevant records and dropped from further follow-up.…”
Section: Study Populationmentioning
confidence: 99%
“…Each year, over 500,000 women die as a result of complications associated with pregnancy around the world [7]. Most maternal deaths result from direct medical causes [8]. The health of women during pregnancy, childbirth, and the postnatal period is referred to as maternal health [9].…”
Section: Introductionmentioning
confidence: 99%
“…Periyasamy K. [8] conducted "a study and revealed that the prevalence of high-risk pregnancies among Indian women was 49.4%, with 33% of women having a single high-risk, and 16.4% having multiple high-risk pregnancies. Notably, pregnant women from Meghalaya and Manipur states had 67.8% and 66.7% with one or more high-risk factors, respectively.…”
Section: Introductionmentioning
confidence: 99%